Penyuluhan Hukum tentang Kenakalan Remaja dan Penanganannya - Aryani, Esti; Triwanto, Triwanto (Empowerment, 2021)
Counseling about juvenile delinquency and its handling to students is very important, given the increasing number of juvenile delinquency during the Covid-19 pandemic. As part of the young generation who are the nation’s successors, students need to be equipped with insights about the importance of building a strong mental attitude so that they are not easily influenced and fall in delinquent behaviour that leads to criminal acts. Counseling is carried out online using the Microsoft Team application. Interactive discussions resulted in conclusions about preventive, repressive, and curative efforts in dealing with juvenile delinquency.